2020
DOI: 10.1097/fjc.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Implications of Nitrite in Hypertension

Abstract: Nitrite, an anion produced from the oxidative breakdown of nitric oxide (NO), has traditionally been viewed as an inert molecule. However, this dogma has been challenged with the findings that nitrite can be readily reduced to NO under pathological conditions, hence representing a physiologically relevant storage reservoir of NO either in the blood or tissues. Nitrite administration has been demonstrated to improve myocardial function in subjects with heart failure and to lower the blood pressure in hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 169 publications
0
4
0
Order By: Relevance
“…Nitric oxide (NO) and nitrite are the intermediate metabolites in nitrogen metabolism. Nitrite can be converted into NO under pathological conditions and therefore represents a physiologically relevant NO capacity in blood or tissue . NO produced physiologically has a useful function in the cardiovascular system, including controlling the vascular tone, leukocyte adhesion, and platelet aggregation. , In addition, NO also has anti-inflammatory and antioxidant effects. , The T cell receptor signaling pathway is the vital regulated pathway because it controls the oxygen diffusion to the central part of the heart …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) and nitrite are the intermediate metabolites in nitrogen metabolism. Nitrite can be converted into NO under pathological conditions and therefore represents a physiologically relevant NO capacity in blood or tissue . NO produced physiologically has a useful function in the cardiovascular system, including controlling the vascular tone, leukocyte adhesion, and platelet aggregation. , In addition, NO also has anti-inflammatory and antioxidant effects. , The T cell receptor signaling pathway is the vital regulated pathway because it controls the oxygen diffusion to the central part of the heart …”
Section: Results and Discussionmentioning
confidence: 99%
“…Nitrite can be converted into NO under pathological conditions and therefore represents a physiologically relevant NO capacity in blood or tissue. 39 NO produced physiologically has a useful function in the cardiovascular system, including controlling the vascular tone, leukocyte adhesion, and platelet aggregation. 40,41 In addition, NO also has anti-inflammatory and antioxidant effects.…”
Section: Resultsmentioning
confidence: 99%
“…NO is known to be a potent vasodilator and regulator of blood pressure, and its endogenous anionic oxidation products, nitrate and nitrite, are increasingly demonstrating antihypertensive activity. [131][132][133] The nitrate-nitrite-NO bioconversion cascade is central to the blood pressure effects of nitrate-nitrite therapies. Nitrate's antihypertensive activity requires its reduction to nitrite, which largely occurs via oral commensal bacteria after ingestion of nitrate-rich foods, such as leafy green vegetables or beetroot.…”
Section: Therapeutics Targeting and Improving No Signaling And Redox ...mentioning
confidence: 99%
“…While many studies have shown the biological significance of NO metabolites at physiological levels [ 7 , 8 ], evidence has accumulated supporting the idea that pharmacological approaches aimed at increasing their tissue concentrations can lead to beneficial effects in various pathological conditions [ 9 , 10 ]. In this context, the oral administration of nitrite leads to increases in plasma concentrations of nitrite, nitrate, and S-nitrosothiols, accompanied by corresponding elevations in NO metabolite concentrations across various organs at different time frames [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%